Determination of possible responses of Radon-222, magnetic effects, and total electron content to earthquakes on the North Anatolian Fault Zone, Turkiye: an ARIMA and Monte Carlo Simulation - Mohammed, Dawar Hama Khalid; Kulahci, Fatih; Muhammed, Ahmad (Springer, 2021)
Around the world, earthquake forecasting studies have become very important nowadays due to the increase in number of fatal earthquakes annually. This paper proposes to achieve a possible relationship between soil radon gas concentration and atmospheric total electron content (TEC) during earthquakes taking into account magnetic effects on the North Anatolian Fault Zone (NAFZ) in Turkiye. The ARIMA and Monte Carlo simulation (MCS) are employed for determining radon gas concentrations by taking into account magnetic effects as an innovative approach. In the study area, relatively small and medium-scale earthquakes have taken place during the observation period. As a result of the investigations, the relationships between each of the parameters and earthquakes are determined; hence, a good relationship is obtained between Rn gas anomaly and micro-seismic activity. In the ionosphere, geomagnetic activity has a primary impact and long duration on TEC distribution, but due to micro-seismic events it has rather small influence. The proposed ARIMA and MCS simulations to detect changes in soil Rn gas concentrations have significant results for detecting micro-seismic activity anomalies.
Keywords: Radon gas; Total electron content; Forecasting; Earthquake; Prediction; ARIMA; Monte Carlo simulation; Model